2021
DOI: 10.1002/stem.3332
|View full text |Cite
|
Sign up to set email alerts
|

SMAD-specific E3 ubiquitin ligase 2 promotes angiogenesis by facilitating PTX3 degradation in MSCs from patients with ankylosing spondylitis

Abstract: Dysregulated angiogenesis of mesenchymal stem cells (MSCs) is closely related to inflammation and disrupted bone metabolism in patients with various autoimmune diseases. However, the role of MSCs in the development of abnormal angiogenesis in patients with ankylosing spondylitis (AS) remains unclear. In this study, we cultured human umbilical vein endothelial cells (HUVECs) with bone marrow-derived MSCs from patients with AS (ASMSCs) or healthy donors (HDMSCs) in vitro. Then, the cocultured HUVECs were assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Accumulating evidence shows that an overabundance of PTX3 is linked to a poor prognosis of cancer and contributes to acquired cancer invasion 37 38. PTX3 is also involved in autoimmune diseases, including RA, SLE and ankylosing spondylitis (AS) 24 39 40. In our study, we determined that PTX3 expression was increased in FLSs and synovium from patients with RA, and PTX3 knockdown decreased the migration and invasion of RA FLSs.…”
Section: Discussionmentioning
confidence: 72%
“…Accumulating evidence shows that an overabundance of PTX3 is linked to a poor prognosis of cancer and contributes to acquired cancer invasion 37 38. PTX3 is also involved in autoimmune diseases, including RA, SLE and ankylosing spondylitis (AS) 24 39 40. In our study, we determined that PTX3 expression was increased in FLSs and synovium from patients with RA, and PTX3 knockdown decreased the migration and invasion of RA FLSs.…”
Section: Discussionmentioning
confidence: 72%
“…Ub-modification was observed on 2 of the 7 lysine residues of ubiquitin, Lys48 Ub and Lys63 Ub , with the latter constituting 95% of the total spectral counts (Figure A–C). This was expected since many of the NEDD4 family E3 ligases have been shown to facilitate Lys63-linkage. To complement the LC/MS/MS analysis, we performed in vitro ubiquitination assays with mutated Ub proteins in the following situations: Lys48 mutated to an arginine (Ub K48R ), Lys63 mutated to an arginine (Ub K63R ) and a double mutant where both Lys48 and Lys63 are mutated to arginine residues (Ub K48/63R ). The Ub pattern of Na V 1.7 CT in the presence of Ub WT was similar to that seen in Figure C,D.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we showed total ubiquitination of ChREBP. Based on a recent report that Smurf2 mediates K48-linked ubiquitination of PTX3 [ 55 ], we expect that ChREBP also has K48-linked ubiquitination. Further studies are needed to accurately determine the ubiquitinated bands of ChREBP.…”
Section: Discussionmentioning
confidence: 99%